Interventions for improving self-direction in people with dementia: a systematic review - Döpp, Carola M. E. (BMC Geriatr, 2021)
BACKGROUND: Dementia is a progressive disease that affects people’s everyday functioning, including the ability to express values, needs and wishes, which can be considered key elements of self-direction. For the purpose of this review, self-direction refers to the organization and/or coordination of your own life, including professional and other care, with the objective of having what you perceive to be a good life. The aim of this systematic review was to assess and describe interventions that aim to improve self-direction of people with dementia. METHODS: A systematic search was conducted in PubMed, Embase, CINAHL, PsycInfo and the Cochrane Library. Empirical studies up to April 2020 were included that used qualitative and/or quantitative methods and reported on interventions for people with dementia aimed at improving self-direction. Stepwise study selection and the assessment of methodological quality were conducted independently by two authors. Data on study and intervention characteristics, outcomes related to self-direction and well-being of people with dementia and factors influencing the feasibility were extracted systematically and described narratively. RESULTS: Ten studies were identified describing a total of nine interventions. Interventions varied in terms of goals, content, target population and duration. Overall, interventions consisted of multiple components focusing on identifying “Who am I?” (beliefs, strengths, values, goals), identifying “What is important to me?” (meaningful activities and goal setting) and/or communicating about preferences with professionals and/or caregivers. The review provides indications that people with dementia may benefit from the interventions included. Overall, positive effects were found in studies on outcomes related to self-direction and wellbeing. However, outcomes measured using quantitative methods showed inconsistent effects between the studies. CONCLUSIONS: Although the methodological quality of all the studies included was ‘good’ or at least ‘fair’, the evidence base of interventions aiming to improve self-direction is still limited due to the low number of studies, the low number of participants and the frequent use of and their authors’ own non-standardized measures. Nevertheless, the review points towards positive effects on self-direction and well-being. Identifying individual beliefs, strengths, values, goals and meaningful activities can be essential components of these interventions, as well as communication about the desired care and support. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12877-021-02133-w.